ANALISIS FAKTOR-FAKTOR PENDORONG PENYEBAB TERJADINYA KEMACETAN DI KAWASAN PAJUS PADANG BULAN MEDAN - Emia Maha (Geography Education Study Program, Universitas Samudra, 2022)
The occurrence of congestion is the result of an imbalance in the traffic network, namely the presence of a vehicle that causes disruption of mobility. The Pajus Padang Bulan area in Medan is close to the University of North Sumatra, so this area is a dominant development location providing learning equipment. This study aims to determine: (1) the factors causing traffic congestion in the Pajus Padang Bulan area (2) efforts to reduce traffic congestion in the Pajus Padang Bulan area, Medan. The results of the location analysis, the main cause of congestion in the Pajus Padang Bulan area of ​​Medan is due to the parking lot which causes traffic lanes to become narrow and obstructed. The method used in this research is direct observation and literature study. The impact resulting from the occurrence of congestion causes a lot of losses both in terms of material, time and energy. From the economic aspect of congestion, the distribution process from the health aspect of congestion has a negative impact, namely affecting the physical and psychological conditions of traffic users.